Utilization of the Riyu Exambro Application as a Learning Evaluation Media - Habibi Nur Rohman Syidiq; Nurul Latifatul Inayati (Yayasan Letiges Konsultan Sosial, 2024)
This study aims to determine the implementation of the evaluation of Al-Islam, Muhammadiyah, and Arabic Learning (ISMUBA) using the Riyu Exambro application. The approach used in this research is a phenomenological qualitative approach. Data collection was carried out using observation, interviews, and documentation. Data analysis techniques were used to reduce and present data and draw conclusions. The results showed that the implementation of ISMUBA learning includes determining the curriculum, making teaching modules, and evaluation. ISMUBA learning evaluation at SMP Muhammadiyah 7 Colomadu Superior Program uses the Riyu Exambro application. The process of evaluating ISMUBA learning with Riyu Exambro at SMP Muhammadiyah 7 Colomadu Superior Program is carried out through several stages, including making grids, questions, and answer keys, archiving questions, creating links, socializing the implementation of exams to students, registering personal data and using tokens by students, working by students, and finally recording scores. Using the Riyu Exambro application as an online evaluation platform provides advantages in preventing cheating, training IT problems, disciplining students, and providing flexible work formats. This study also identified several obstacles, such as technical problems related to Arabic fonts, unstable internet signals, application screens that are often refreshed, and the need for devices and limited internet access.